LEMBAR KERJA MAHASISWA BERBAHASA INGGRIS BERBASIS DISCOVERY LEARNING DALAM PEMBELAJARAN SAINS LINGKUNGAN - Ramdani, Akhmad Subkhi; Mardiyah, Mutmainatul; Ichsan, Ilmi Zajuli (FKIP Universitas Tanjungpura, 2025)
The problem of 21st century education is one of them related to creative thinking skills. Learning activities that prioritize creative learning are usually seen when a search activity occurs. Creative learning based on discovery learning becomes a new innovation through the development of student worksheets. The purpose of this study is to develop English language student worksheets integrated with discovery learning in environmental science topics. The method used in this study is research and development (R&D) with the stages of development analyze, design, develop, implement, evaluate (ADDIE). This development method is carried out until the develop stage. The results of this study indicate that the student worksheets that have been developed have a category that is suitable for use in learning. Student worksheets are crucial for developing students' understanding of science and environmental learning. Students worksheets integrated with English and discovery learning are relevant to the needs of the 21st century. The educational innovation developed in this study needs to be further developed in the form of other products in the future.